2021
DOI: 10.23887/jet.v5i4.40986
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny on Indonesian EFL Teachers’ Willingness to Understand and Implement the TPACK in VLE

Abstract: During this pandemic, all countries focused on the issue of transforming the education system, media, teaching strategies, and materials, from face-to-face teaching and learning to teach in a Virtual Environment (TVE)-based, including in Indonesia. However, this sudden change of situation made all education systems change in a hurry. The fact that English teachers are more proficient at applying their content and pedagogical knowledge than technological knowledge makes this study aim to determine how willing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The same thing also occurs to other study which it's finding overview that the TPACK level development in their study was still not fully achieved by the teachers [19]. A study conducted by Surayya, Asrobi, and Farizi has found that most Indonesian EFL teachers are at the median level of readiness to learn and practice TPACK [4]. They conducted a survey which the result shows that only 23% participants have a strong willingness to understand the TPACK.…”
Section: Statistical Validationsupporting
confidence: 63%
See 2 more Smart Citations
“…The same thing also occurs to other study which it's finding overview that the TPACK level development in their study was still not fully achieved by the teachers [19]. A study conducted by Surayya, Asrobi, and Farizi has found that most Indonesian EFL teachers are at the median level of readiness to learn and practice TPACK [4]. They conducted a survey which the result shows that only 23% participants have a strong willingness to understand the TPACK.…”
Section: Statistical Validationsupporting
confidence: 63%
“…Meanwhile, 63% participants at moderate level which indicate their TPACK at middle level. This study concludes that most of the EFL teachers have middle willingness in understanding TPACK and needs some encouragement on their internal motivation through providing some trainings and real context practice about TPACK by government and their internal institution [4]. The clearer result of statistical analysis of satisfaction level of the online classes can be seen in Table 2 and Table 3…”
Section: Statistical Validationmentioning
confidence: 67%
See 1 more Smart Citation
“…Adherents of the flow of behaviorism pay attention to the function of incentives and punishments in sustaining or lessening the tendency for specific behaviors to arise in this perspective (Aini, Muslem, & Marhaban, 2021). A devotee of behaviorism, for example, will examine environmental disturbances that are thought to be relevant to the problem (Surayya, Asrobi, & Farizi, 2021). Adherents of the social cognitive learning perspective hypothesis, on the other hand, attempt to blend various parts of behaviorism with studies on thoughts, values, expressions, and intents (Sandi Sukandi, 2022).…”
Section: Introductionmentioning
confidence: 99%